2009
DOI: 10.1093/aje/kwp354
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiation Risk Factors for Thyroid Cancer in the US Radiologic Technologists Study

Abstract: The incidence of thyroid cancer has been rapidly increasing in the United States, but few risk factors have been established. The authors prospectively examined the associations of self-reported medical history, anthropometric factors, and behavioral factors with thyroid cancer risk among 90,713 US radiologic technologists (69,506 women and 21,207 men) followed from 1983 through 2006. Incident thyroid cancers in 242 women and 40 men were reported. Elevated risks were observed for women with benign thyroid cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
185
5
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(214 citation statements)
references
References 50 publications
15
185
5
9
Order By: Relevance
“…Epidemiological studies have consistently reported that individuals who are either overweight or obese are at an increased risk of thyroid cancer (23)(24)(25)(26)(27). The increasing trend of obesity might be another factor that accounts for some of the observed increasing incidence of thyroid cancer, although the degree of its contribution is unclear.…”
Section: Thyroid Cancer Epidemic 477mentioning
confidence: 99%
“…Epidemiological studies have consistently reported that individuals who are either overweight or obese are at an increased risk of thyroid cancer (23)(24)(25)(26)(27). The increasing trend of obesity might be another factor that accounts for some of the observed increasing incidence of thyroid cancer, although the degree of its contribution is unclear.…”
Section: Thyroid Cancer Epidemic 477mentioning
confidence: 99%
“…A reduced risk of thyroid gland cancer due to cigarette smoking status has been found in several studies [1][2][3]45]. Mack et al performed an international pooled analysis of 14 case-control studies and found 40% reduction in risk of papillary and follicular thyroid cancers among current smokers compared to never smokers.…”
Section: Thyroid Gland Cancermentioning
confidence: 99%
“…Recent studies showed that the risk of thyroid cancer was significantly increased by excess body weight, either overweight or obesity (Meinhold et al 2010, Aschebrookcancer (PTC), Kim et al (2013a) found that a higher BMI was correlated with a more aggressive PTC phenotype, such as increased tumor size, extrathyroidal invasion, and advanced disease stage, independent of age, sex, and other confounding factors. While compelling epidemiological data support the positive correlation of obesity with increased risk thyroid cancer, the molecular mechanisms by which obesity increase the risk of thyroid cancer progression are poorly understood.…”
Section: Introductionmentioning
confidence: 99%